2013
DOI: 10.1186/1471-2199-14-26
|View full text |Cite
|
Sign up to set email alerts
|

MAR-mediated integration of plasmid vectors for in vivo gene transfer and regulation

Abstract: BackgroundThe in vivo transfer of naked plasmid DNA into organs such as muscles is commonly used to assess the expression of prophylactic or therapeutic genes in animal disease models.ResultsIn this study, we devised vectors allowing a tight regulation of transgene expression in mice from such non-viral vectors using a doxycycline-controlled network of activator and repressor proteins. Using these vectors, we demonstrate proper physiological response as consequence of the induced expression of two therapeutica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…We decided to use a weekly administration regimen to obtain maximum and sustained GAA levels based upon the transient nature of non-viral GT and short-term episomal longevity. Similar to in vitro transfection, maximum expression and maintenance may be only 3-14 days before the plasmid is lost however long term detection has been observed (109)(110)(111)(112)(113)(114)(115)(116)(117)(118)(119)(120)(121)(122)(123)(124). We have From DNA vaccine (182)(183)(184)(185), the production of the recombinant protein may be released into the circulation and taken up by distant tissues, functioning as an "enzyme-factory or depot."…”
Section: % Of Normal (Unpublished)mentioning
confidence: 99%
See 1 more Smart Citation
“…We decided to use a weekly administration regimen to obtain maximum and sustained GAA levels based upon the transient nature of non-viral GT and short-term episomal longevity. Similar to in vitro transfection, maximum expression and maintenance may be only 3-14 days before the plasmid is lost however long term detection has been observed (109)(110)(111)(112)(113)(114)(115)(116)(117)(118)(119)(120)(121)(122)(123)(124). We have From DNA vaccine (182)(183)(184)(185), the production of the recombinant protein may be released into the circulation and taken up by distant tissues, functioning as an "enzyme-factory or depot."…”
Section: % Of Normal (Unpublished)mentioning
confidence: 99%
“…If plasmid related cytotoxicity is found, we will remove CpG dimer sequences by minicircle synthesis (182,185). We also hypothesize there will be positive selective pressure to maintain the plasmid in tissues to be "healthier" by being able to hydrolyze glycogen to glucose (109)(110)(111)(112)(113)(114)(115)(116)(117)(118)(119)(120)(121)(122)(123)(124)(125)(126)(149)(150)(151). In some studies, plasmid integration into chromosomes was observed, however integration has the potential to cause tumorigenic events (109)(110)(111)(112)(113)(114)(115)(116)(117)(118)(119)(120)(121)(122)(123)(124)(125)(126)(149)(150)(151).…”
Section: % Of Normal (Unpublished)mentioning
confidence: 99%
“…If this is realized, autologous transplantation will be possible for curing the dysfunction muscle tissue. In contrast, direct gene-transfer-based therapy has some limitations, as exemplified by transgene silencing issues (mentioned in Section 2.4.4) as well as the difficulty in mediating systemic and sustained dystrophin expression [84].…”
Section: Application To Gene Therapymentioning
confidence: 99%
“…S/MAR effectively protects transgene expression from repression (barrier activity) and also supports a higher level of transcription from promoters within expression vectors (stimulatory activity) [ 144 ]. Several S/MARs are capable of increasing the efficacy of vector construct integration into chromosomes [ 147 , 148 ]. Moreover, S/MAR proteins are able to provide integration of new additional copies of the vector construct in a region already containing integrated construct copies.…”
Section: Enhancing Transgene Expression Using A/t-rich Sequences Assomentioning
confidence: 99%